Original Antigenic Sin Response to RNA Viruses and Antiviral Immunity - Park, Mee Sook (Immune Netw, 2016)
The human immune system has evolved to fight against foreign pathogens. It plays a central role in the body's defense mechanism. However, the immune memory geared to fight off a previously recognized pathogen, tends to remember an original form of the pathogen when a variant form subsequently invades. This has been termed 'original antigenic sin'. This adverse immunological effect can alter vaccine effectiveness and sometimes cause enhanced pathogenicity or additional inflammatory responses, according to the type of pathogen and the circumstances of infection. Here we aim to give a simplified conceptual understanding of virus infection and original antigenic sin by comparing and contrasting the two examples of recurring infections such as influenza and dengue viruses in humans.